Acute Radiation Effects, the H-ARS in the Non-human Primate: A Review and New Data for the Cynomolgus Macaque with Reference to the Rhesus Macaque. Issue 4 (October 2021) - Farese, Ann M.; Drouet, Michel; Herodin, Francis; Bertho, Jean-Marc; Thrall, Karla D.; Authier, Simon; Doyle-Eisele, Melanie; MacVittie, Thomas J.
Abstract: Medical countermeasure development under the US Food and Drug Administration animal rule requires validated animal models of acute radiation effects. The key large animal model is the non-human primate, rhesus macaque. To date, only the rhesus macaque has been used for both critical supportive data and pivotal efficacy trials seeking US Food and Drug Administration approval. The potential for use of the rhesus for other high priority studies such as vaccine development underscores the need to identify another non-human primate model to account for the current lack of rhesus for medical countermeasure development. The cynomolgus macaque, Macaca fascicularis, has an existing database of medical countermeasure development against the hematopoietic acute radiation syndrome, as well as the use of radiation exposure protocols that mimic the likely nonuniform and heterogenous exposure consequent to a nuclear terrorist event. The review herein describes published studies of adult male cynomolgus macaques that used two exposure protocols—unilateral, nonuniform total-body irradiation and partial-body irradiation with bone marrow sparing—with the administration of subject-based medical management to assess mitigation against the hematopoietic acute radiation syndrome. These studies assessed the efficacy of cytokine combinations and cell-based therapy to mitigate acute radiation-induced myelosuppression. Both therapeutics were shown to mitigate the myelosuppression of the hematopoietic acute radiation syndrome. Additional studies being presented herein further defined the dose-dependent hematopoietic acute radiation syndrome of cynomolgus and rhesus macaques and a differential dose-dependent effect with young male and female cynomolgus macaques. The database supports the investigation of the cynomolgus macaque as a comparable non-human primate for efficacy testing under the US Food and Drug Administration animal rule. Critical gaps in knowledge required to validate the models and exposure protocols are also identified.